A New Species of Marine Leeches (Hirudinea, Piscicolidae) from the Coastal Waters of South Africa - Utevsky, A.Yu. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Описана морская рыбья пиявка Austrobdella oosthuizeni A. Utevsky, sp. n. из прибрежных вод Южной Африки. Экземпляры достигают длины 9,7 мм, трахелосома субцилиндрическая, уросома уплощенная без боковых пузырей; тело не пигментировано, полупрозрачное; глаза и глазки отсутствуют (у фиксированных экземпляров). Все экземпляры собраны с лобстера Jassus lalandii (Crustacea, Decapoda). The marine piscicolid leech Austrobdella oosthuizeni A. Utevsky, sp. n. from the coastal waters of South Africa is described and illustrated. The body is up to 9.7 mm long, trachelosome subcylindrical, urosome flattened without pulsatile vesicles; body unpigmented, semitransparent; eyes and ocelli absent (in fixed specimens). The specimens were collected on Jassus lalandii (Crustacea, Decapoda).